EFEKTIVITAS TEKNIK MODELING DALAM MENINGKATKAN KEMATANGAN KARIR PESERTA DIDIK - Djoni dan Solihatun Aminudin (Faktor Jurnal Ilmiah Kependidikan, 2014)
Abstract: Mechanical modelling is a technique that is implemented from social learning theory. This theory explains how human behavior in terms of continuous reciprocal interaction between cognitive, behavioral, and environmental influences. Learning through modeling include the addition of a search and the observed behavior, and then to generalize from one observation to another observation. This study aims to determine the effectiveness of Modeling Techniques to Enhance Career Maturity Learners SMA PKBM Negeri 12 East Jakarta in class XI in the school year 2013-2014. The method used in this study is the method of experiment. With a design that is used is the Pre-Experimental Design. Forms Pre-Experimental Design used is "One-group pretest-posttest design". Techniques of data collection using questionnaires and observation guidelines were developed by the researcher. The results showed that there is a mean difference between the high rate of career maturity before and after the test. Pre-test career maturity has an average 90.80. While Maturity career post-test of 107.73. Furthermore, the results of this study it can be concluded that the Effective Modeling Techniques to Enhance Career Maturity of Students at SMA PKBM Negeri 12 East Jakarta.  Keywords: Modeling Techniques, Career Maturity.